"We want the earth." motto of class of 91 - Morse, John Otis (My University, 1891)
Introduction: At first thought, it may appear that our motto is more of a joke, than a real earnest expression of the ambitions of the class. Some think that it was adopted in fear; and we have even been accused of having stolen it from the Alliance. But while it is not classic, not clothed in a later phrase, while some may think it almost vulgar, it at least has the virtue of being plain English. We have turned from the beaten path of college classes, and have adopted a motto that means work and success. It has long been assumed that college graduates are not practical in life; that often they are less successful than those who have poorer opportunities, that they deal in theories, and hold themselves aloof from the real work of the world. But we go from our college course with the declaration that “we want the earth”. This is not an idle expression. It means more than the mere literal interpretation. The word, “want”, when rightly used, does not mean to sit with folded hands until someone makes us a present. But it means that we are ready to work, ready to use the energy and ability of a college training in getting, and in making the object of our wants worth having. It means that we are ready to bring practical life and college education together, ready to use the latter only as a means of being more of factual in the work of life, not as an end in its self.
Citation: Morse, John Otis. "We want the earth." motto of class of 91. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Class motto; Success; Business; Theses; Manuscripts (documents)